The comparison of the exercise stress test tolerance using Bruce and Balke-Ware protocols in Malaysians - Jaafar, Zulkarnain; Mokhtar, Abdul Halim; Abdul Hamid, Mohamad S.; Ali, Mohamed Razif Mohamed (Edizioni Minerva Medica, 2019)
BACKGROUND: The issue of premature termination of exercise stress test in Asian people due to intolerance to rapid exercise workload increment in Bruce protocol has been pointed out. In this study, we want to compare the exercise stress test tolerance using Bruce and Balke-Ware protocols. METHODS: This was a cross-over experimental study involving 30 male subjects aged 40 to 65 performing exercise stress test using Bruce and Balke-Ware protocols. Hemodynamic responses, electrocardiographic pattern and exercise duration were monitored during the test and the reason for termination was recorded. RESULTS: Bruce protocol achieved equivalent hemodynamic responses, completion rate and test findings to Balke-Ware (P>0.001). Over 50% of the subjects were able to complete the stress test using both protocols. 46.7% (N.=14) of subjects terminate the test prematurely for Bruce and 50% (N.=15) for Balke-Ware protocol. Fatigue was the commonest cause with (57.2% N.=8, 60% N.=9), followed by achieved target heart rate (35.5% N.=5, 33.3% N.=5) and shortness of breath (7.1% N.=1, 6.7% N.=1) for Bruce and Balke-Ware respectively. The exercise capacity (metabolic equivalent) attained during exercise was similar in both protocol (P>0.001), and exercise duration in Balke-Ware was significantly longer than the Bruce protocol (P<0.001). CONCLUSIONS: We found that protocol selection does not affect the completion rate and outcome of the exercise stress test and their tolerance was similar regardless of the protocols used. For Asian peoples who were unable to complete the exercise stress test due to any reasons, their cardiac status is best evaluated using other methods. © 2018 EDIZIONI MINERVA MEDICA.